LINGUOCULTURAL REPRESENTATION OF PATRIOTISM IN POETIC DISCOURSE - Durdona Ochilova Fakhridin kizi; Nasiba Narzullayevna Sidikova (Modern World Education: New Age Problems – New solutions, 2026)
This article investigates the linguocultural representation of patriotism in poetic discourse. Patriotism is approached not only as an emotional attachment to one’s homeland but also as a culturally constructed concept shaped by history, collective memory, and national worldview. From a linguoculturological perspective, language serves as a medium through which cultural meanings and values are encoded, preserved, and transmitted. Poetic discourse, characterized by metaphorical and symbolic expression, provides a particularly rich field for exploring patriotic meanings. The study analyzes linguistic and stylistic means used to verbalize the concept of the homeland and examines how these means reflect cultural models of identity and belonging. The findings indicate that patriotic motifs in poetry function as a cultural code that shapes national consciousness and reinforces collective values. The research contributes to the understanding of the interaction between language, culture, and literature in the formation of cultural concepts.